Laporan Keuangan Distributor Makanan Berdasarkan Standar Akuntansi Keuangan Entitas Mikro, Kecil, dan Menengah - Etika Dwi Novitasari; Arik Susbiyani; Moh. Halim (BUDGETING : Journal of Business, Management and Accounting, 2022)
The purpose of this study was to analyze the financial statements of CV Food Distributors. TKT Bana Food Jember is based on financial accounting standards for micro, small and medium entities. This research method is descriptive qualitative. The data obtained in this study were based on observations, interviews, and documentation. Sources of data obtained in this study are primary and secondary data sources. The results showed, the standards used by Food Distributors CV. TKT Bana Food Jember is still not clearly stated, Food Distributor CV. TKT Bana Food Jember admits that they are still not very deep in using the standard. Conclusion, recording, acknowledging, measuring and presenting the financial statements of CV Food Distributors. TKT Bana Food Jember is still not in accordance with SAK EMKM. Keywords: Recording, Recognition, Measurement and Presentation of Financial Statements